The Role of Accounting Services in Small and Medium Scale Businesses in Nigeria - Obiamaka Nwobu; Samuel O. Faboyede; Anthony T. Onwuelingo (Journal of Accounting, Business and Management (JABM), 2015)
In several countries of the world, the government requires the input of Small and Medium Scale Enterprises (SMEs) for economic growth and job creation. This study examines the approach of small scale entrepreneurs when utilizing accounting services in Nigeria. The aim of this study is to examine the reasons for Small Scale Entrepreneurs (SSEs) employment of accounting services. Secondly, this study seeks to decipher the benefits of SSEs engagement of accounting services from the perspective of the managers of such business enterprises in Nigeria. A survey instrument was administered to one hundred and twenty (120) respondents in Lagos State and Ogun State, Nigeria. The test of reliability of the questionnaire was carried out using Cronbach's alpha, which resulted in a coefficient of 0.773. On the basis of the coefficient, the research instrument is reliable. The study finds that SSEs employ accounting services for better accountability, correct determination of profit, to help management reach set goals and objectives. Some of the benefits of employing accounting services as identified by respondents include increased accountability of business operations, reduced fraud, correct measurement of profit, achievement of managements' set goals. From these findings, we recommend that accountants explore the large market ahead of them in small and medium scale enterprises.